2020
DOI: 10.3389/fped.2020.00252
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Least Invasive Management of Pelvi-Ureteric Junction Obstruction in Children: A Critical Literature Review of Comparative Outcomes

Abstract: Introduction: To review the published evidence on the minimally invasive pyeloplasty techniques available currently with particular emphasis on the comparative data about the various minimally invasive alternatives to treat pelvi-ureteric junction obstruction and gauge if one should be favored under certain circumstances. Materials and Methods: Non-systematic review of literature on open and minimally invasive pyeloplasty including various kinds of laparoscopic procedures, the robotic-assisted laparoscopic pye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Costs of robot-assisted surgical procedures are in general higher than in regular laparoscopic surgery, due to investment and maintenance costs of the robot. In a critical literature review of comparative outcomes reported for the least invasive management of ureteropelvic obstruction in children, a Spanish group found two major drawbacks of robotic-assisted laparoscopic pyeloplasty in children: costs and the size of instruments [20]. This might be true for the Da Vinci robotic system.…”
Section: Discussionmentioning
confidence: 99%
“…Costs of robot-assisted surgical procedures are in general higher than in regular laparoscopic surgery, due to investment and maintenance costs of the robot. In a critical literature review of comparative outcomes reported for the least invasive management of ureteropelvic obstruction in children, a Spanish group found two major drawbacks of robotic-assisted laparoscopic pyeloplasty in children: costs and the size of instruments [20]. This might be true for the Da Vinci robotic system.…”
Section: Discussionmentioning
confidence: 99%
“…Robot-assisted laparoscopic surgery was first developed for use in adult patients but is now also applied in pediatric surgery. Robot-assisted laparoscopic surgery is well suited to operations that require fine dissection or suturing in small anatomic spaces [7] and has been used successfully in the management of pediatric hydronephrosis [8,9]. However, the operation requires extensive preparation of the gastrointestinal tract, use of the Trendelenburg position and a CO2 pneumoperitoneum, and surgery is associated with non-negligible risks of perioperative pneumoperitoneum-related complications, hypothermia, pressure injury, and scald injury.…”
Section: Introductionmentioning
confidence: 99%
“…Pyelo-ureteral junction obstruction (PUJO) is a common condition in children and adults alike and pyeloplasty the standard treatment. 13…”
Section: Introductionmentioning
confidence: 99%
“…Pyelo-ureteral junction obstruction (PUJO) is a common condition in children and adults alike and pyeloplasty the standard treatment. [1][2][3] Usually, the first sign of PUJO is the radiological detection of hydronephrosis (HN) on an ultrasound (US) scan. HN is a very common finding in general.…”
Section: Introductionmentioning
confidence: 99%